Упростите выражение             6         +                1             x  a(квадрат)+6a+9                                     (  -------------          -------------------- ) ------------------------------                    ...

Упростите выражение             6         +                1             x  a(квадрат)+6a+9                                      (  -------------          -------------------- ) ------------------------------                                       a(квадрат) - 9        3-a                              5
Гость
Ответ(ы) на вопрос:
Гость
1)6\а2-9 + (1\3-а)=6\(а-3)*(а+3) -1\а-3 = 6-(а+3) \(а-3)*(а+3)=6-а-3\(а-3)*(а+3)=3-а\(а-3)*(а+3) \-(а-3)\(а+3)*(а-3)=-1\а+3 2)-1\а+3 *(а2+6а+9\5) =-1\а+3*((а+3) в кв \5) = -(а+3)\5=-а-3\5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы